Pancreatitis, panniculitis and polyarthritis (PPP-) syndrome caused by post-pancreatitis pseudocyst with mesenteric fistula: diagnosis and successful surgical treatment : case report and review of literature - Dieker, Wulf; Derer, Johannes; Henzler, Thomas; Schneider, Alexander; Rückert, Felix; Wilhelm, Torsten; Krüger, Bernd (International journal of surgery case reports, 2017)
INTRODUCTION: Pancreatitis, panniculitis and polyarthritis syndrome is a very rare extra-pancreatic complication of pancreatic diseases. PRESENTATION OF CASE: While in most cases this syndrome is caused by acute or chronic pancreatitis, we report a case of a 62-year-old man presenting with extensive intraosseous fat necrosis, polyarthritis and panniculitis caused by a post-pancreatitis pseudocyst with a ﬁstula to the superior mesenteric vein and extremely high blood levels of lipase. This became symptomatic 2.5 years after an episode of acute pancreatitis and as in most cases abdominal symptoms were absent. Treatment by surgical resection of the pancreatic head with the pseudocyst and mesenteric ﬁstula led to complete remission of all symptoms. DISCUSSION: A review of the literature revealed that all publications are limited to case reports. Most authors hypothesize that an unspeciﬁc damage can cause a secretion of pancreatic enzymes to the bloodstream leading to a systemic lipolysis and fat tissue necrosis, especially of subcutaneous tissue, bone marrow, inducing panniculitis, polyarthritis and osteonecrosis. Even if caused by an acute pancreatitis abdominal symptoms are often mild or absent in most cases leading to misdiagnosis and poor prognosis. CONCLUSION: While symptomatic treatment with NSAR and cortisone showed poor to moderate response, causal treatment can be successful depending on the underlying pancreatic disease.